Humanized Mouse Model Mimicking Pathology of Human Tuberculosis for in vivo Evaluation of Drug Regimens - Arrey, Frida; Löwe, Delia; Kuhlmann, Stefanie; Kaiser, Peggy; Moura-Alves, Pedro; Krishnamoorthy, Gopinath; Lozza, Laura; Maertzdorf, Jeroen; Skrahina, Tatsiana; Skrahina, Alena; Gengenbacher, Martin; Nouailles, Geraldine; et al. (Frontiers in Immunology, 2019)
Human immune system mice are highly valuable for in vivo dissection of human immune responses. Although they were employed for analyzing tuberculosis (TB) disease, there is little data on the spatial organization and cellular composition of human immune cells in TB granuloma pathology in this model. We demonstrate that human immune system mice, generated by transplanted human fetal liver derived hematopoietic stem cells develop a continuum of pulmonary lesions upon Mycobacterium tuberculosis aerosol infection. In particular, caseous necrotic granulomas, which contribute to prolonged TB treatment time, developed, and had cellular phenotypic spatial-organization similar to TB patients. By comparing two recommended drug regimens, we confirmed observations made in clinical settings: Adding Moxifloxacin to a classical chemotherapy regimen had no beneficial effects on bacterial eradication. We consider this model instrumental for deeper understanding of human specific features of TB pathogenesis and of particular value for the pre-clinical drug development pipeline.